2020
DOI: 10.2147/lra.s240567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anesthesia Options and the Recurrence of Cancer: What We Know so Far?</p>

Abstract: Surgery is a critical period in the survival of patients with cancer. While resective surgery of primary tumors has shown to prolong the life of these patients, it can also promote mechanisms associated with metastatic progression. During surgery, patients require general and sometimes local anesthetics that also modulate mechanisms that can favor or reduce metastasis. In this narrative review, we summarized the evidence about the impact of local, regional and general anesthesia on metastatic mechanisms and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 134 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…It can reduce the inflammatory response to surgery and thus, cancer recurrence through several mechanisms. Regional anesthesia attenuates the stress response to surgery via pain control or sympathetic blocks, reduces the need for anesthetic agents, and exhibits direct effects by absorption of local anesthetic agents, as described above ( 112 , 113 ). In a prospective study, patients who underwent lung cancer surgery with thoracic epidural anesthesia had significantly lower IL-6 levels in serum and lung epithelial lining fluid ( 114 ).…”
Section: Perioperative Modulation Of Inflammatory Response and Oncolo...mentioning
confidence: 99%
“…It can reduce the inflammatory response to surgery and thus, cancer recurrence through several mechanisms. Regional anesthesia attenuates the stress response to surgery via pain control or sympathetic blocks, reduces the need for anesthetic agents, and exhibits direct effects by absorption of local anesthetic agents, as described above ( 112 , 113 ). In a prospective study, patients who underwent lung cancer surgery with thoracic epidural anesthesia had significantly lower IL-6 levels in serum and lung epithelial lining fluid ( 114 ).…”
Section: Perioperative Modulation Of Inflammatory Response and Oncolo...mentioning
confidence: 99%
“…The problems raised by the clinical tolerance to general anesthesia in OSCC patients can be found elsewhere [46,47]. Besides the different immediate postoperative characteristics induced by the choice of anesthesia [48], specific protocols may change the risk of post-surgical recurrence of cancer, as suggested in various preclinical models (review in Cata et al [45]). The different anesthetics and/or analgesic regimen used in oral surgery can produce direct effects on OSCC cells [49][50][51].…”
Section: Anesthesics and Analgesicsmentioning
confidence: 99%
“…Surgical cancer patients receive general, sometimes local or regional anesthesia, and analgesia [ 45 ]. General anesthesia typically relies on total intravenous anesthesia (propofol) or volatile inhaled anesthesia (isoflurane).…”
Section: Key Perioperative Events and The Relevant Biological Parametersmentioning
confidence: 99%
“…The perioperative use of intravenous or volatile anesthetics may modulate the cancer-promoting/ suppressing signaling network and affect the long-term cancer recurrence and disease-free survivability. Several retrospective studies on different cancer types showed a significant advantage of using total intravenous anesthesia over inhalational anesthesia [131]. A prospective study showed that propofol-epidural anesthesia was associated with longer disease-free survival than sevoflurane/opioids in infiltrating bladder cancer patients undergoing radical tumor cystectomy [132].…”
Section: Influence Of Anesthetics On Survivability and Cancer Recurrencementioning
confidence: 99%